Pengaruh ESG terhadap Risiko Finansial Korporat - Ardhana Reswari Hasna Pratista; Meilani Intan Pertiwi; Moh. Eko Saputro (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to investigate the relationship between corporate ESG assessment and financial risk exposure. Specifically, the authors seek to understand whether corporate financial risk can be influenced by corporate sustainability. With a total of 214 observations from various industrial sectors listed on the Indonesia Stock Exchange (IDX) from 2020-2024, this study empirically tests the relationship between the three dimensions of sustainability, namely environmental, social, and governance, with financial risk. The research findings show that environmental and social values ​​have a significant effect on financial risk. Companies with superior environmental and social performance are considered more robust and resilient in facing external pressures, thus reducing the potential for financial losses that the company may suffer. Meanwhile, governance values ​​do not show a significant effect on financial risk. This means that the corporate governance structure does not have a direct effect on financial risk. The test carried out in this study is a multiple regression test with the help of the Eviews Ver 13 statistical tool.